Iraq Crude Oil Exports – April, May, June/ 2021 - SOMO, Ministry of Oil / Oil Marketing Company (Journal of Petroleum Research and Studies, 2023)
Table 1. Iraq Crude Oil Exports – April 2021 Table 2. Iraq Crude Oil Exports – May 2021 Table 3. Iraq Crude Oil Exports – June 2021